Adverse Effects of Polycystic Ovarian Syndrome on Pregnancy Outcomes in Women With Frozen-Thawed Embryo Transfer: Propensity Score-Matched Study - Ni, Zhexin; Mei, Shanshan; You, Siting; Lin, Yi; Cheng, Wen; Zhou, Ling; Kuang, Yanping; Yu, Chaoqin (Frontiers in Endocrinology, 2022)
Purpose This work aimed to evaluate the adverse effect of polycystic ovary syndrome (PCOS) on pregnancy outcomes of singletons after vitrification in women with frozen-thawed embryo transfer (FET). Methods Patients with/without PCOS who underwent FET from January 2013 and December 2018 were included. Propensity score matching (PSM) was used to reduce the influence of bias. Logistic regression was applied to identify the risk factors of adverse pregnancy outcomes of singletons in women with PCOS. Result After PSM, the PCOS group had shorter gestational age (P<0.001) and lower newborn birth weight than the non-PCOS group (P=0.045). Compared with the non-PCOS group, the PCOS group had an increased risk of gestational diabetes mellitus (GDM) and pregnancy-induced hypertension (PIH) (P<0.001), placenta and membrane abnormality (P<0.001), stillbirth (P<0.001), neonatal complication (P=0.014), and miscarriage rate (P<0.001). Neonatal complication was associated with parity (adjusted OR=1.202, 95% CI=1.002–1.443, P=0.048) and basal P level (adjusted OR=1.211, 95% CI=1.021–1.436, P=0.028). According to multivariable logistic regression analysis, the miscarriage rate was related to parity (adjusted OR=1.201, 95% CI=1.057–1.166, P=0.005) and basal E2 (adjusted OR=1.002, 95% CI=1.000–1.004, P=0.019) and P levels on the day of embryo transfer (adjusted OR=0.971, 95% CI=0.957–0.985, P<0.001). Conclusions Compared with non-PCOS women, women with PCOS have a higher risk of GDM and PIH, and neonatal complications and therefore require additional care during pregnancy and parturition.